Profile and obstetric outcome of teenage pregnancies compared with pregnant adults at a district hospital in KwaZulu-Natal - Olaolu I. Ogunwale; Selvandran Rangiah (South African Family Practice)
Background: Teenage pregnancy remains a major public health concern and a challenge for developing countries. Young maternal age can lead to serious physical, social and psychological consequences as teenage mothers are less likely to gain full educational potential and are at higher risk of poverty and complications of pregnancy. The objective of the study was to describe the profile and obstetric outcome of teenage pregnancy compared with that of pregnant adults at a district hospital in KwaZulu-Natal.